Procedural Text Writing Skills Through the Student Teams-Achievement Divisions (STAD) Learning Model Among Tenth-Grade Students at Senior High School - Ahyar; Sukma; Andi Bismawati (Universitas Islam Negeri Palopo, 2026)
Limited classroom-based evidence has examined how Student Teams-Achievement Divisions (STAD) can support procedural text writing in Indonesian senior high schools, particularly through an iterative classroom-action process. This study investigated the improvement of procedural text writing skills among 28 students in Class X-B 3 at Senior High School through STAD cooperative learning. STAD was selected because its combination of heterogeneous teamwork, shared goals, individual accountability, and peer support can provide structured opportunities for students to discuss text organization and language use. The study employed Classroom Action Research conducted in two cycles comprising planning, action, observation, and reflection. Data were obtained from writing tests, classroom observations, and documentation and analyzed descriptively. Reported classical mastery increased from 35.7% in Cycle I to 85.7% in Cycle II, an increase of 50 percentage points, exceeding the predetermined success criterion of 75% of students achieving the Minimum Mastery Criterion of 75. Classroom observations also indicated more active group participation, clearer allocation of responsibilities, and more focused teacher guidance in Cycle II. The study contributes genre-specific classroom evidence on the use of STAD for procedural text writing and suggests that structured peer interaction can be integrated with explicit writing guidance in Indonesian language instruction.